Electronic textiles functionalized with conductive polymers - Mendes, Bernardo Luís Moura (2019)
Smart textiles have received a lot of attention nowadays for combining two of the most prolific industries: fabrics and electronics. This was possible due to the evolution of conductive polymers, mean-ing that a material as conductive as metals with flexible properties was in the market. Its potential to integrate signals and stimuli from contact means that a myriad of applications might be in the making, spanning interest from electronics to communication, military and biomedical uses. The main goal of this work was to study different methodologies to functionalize commercial textiles with conductive polymers to obtain piezoresistive textiles. Polypyrrole (PPy) and poly(3,4-ethylenedioxythiophene) (PEDOT) are two intrinsically conduc-tive polymers used to functionalize lycra and felt textiles. Such functionalization was carried out by in situ-polymerization of pyrrole (Py) and 3,4-ethylenedioxythiophene (EDOT). Several polymerization con-ditions were evaluated to determine the most suitable ones to prepare stable conductive textiles. In-plane electrical conductivities of 6.707x10−3 Scm−1 to 1.808x10−2 Scm−1 and transversal conductivities of 1.837x10−4 Scm−1 to 2.040x10−3 Scm−1 were reached throughout textiles. Morphological, chemical and electrical characterization was carried before and out after polymerization. Piezoresistive behaviour of textiles was studied, because coated and agglomerated polymer comes into different contacts when stress is applied. Two different approaches were studied: stretch behaviour for elastic lycra ranging from 11-26kΩ and pressure behaviour for felt textiles ranging from 0.72-19.54kΩ. Finally, stability tests were studied. In this section, abrasion was performed to show the wear off textiles. Felt had the best stability with values from 3.903x10−4 S.cm−1 to 6.685x10−6 S.cm−1, while lycra had the worst results, from 1.242x10−4 S.cm−1 to 2.696x10−11 S.cm−1. Conductivity over time was studied, showing there is over a 50% conductivity decline over 6 months. Washing cycles, showed de-clines of over four orders of magnitude, compromising further use.